Visual reaction effects induced and stimulated by different lights on phototactic bio-behaviors in Locusta migratoria manilensis - Qihang, Liu; Zhe, Xin; Qiang, Zhou (International Journal of Agricultural and Biological Engineering, 2017)
Control of locusts traditionally relies on chemical insecticides. However, chemical control had led to serious environment problems, while light trap techniques based on manipulating insect phototactic responses, are proposed to use for plague locusts control. The key to high efficiency of the trap is to decide the photoelectric reaction intensities on the positive phototaxis of insects. The study compared the visual reaction effects of locusts with their phototactic photosensitivity through the use of spectrometry and behavior investigations, to obtain the influences of the visual spectrum characteristics on locusts positive phototaxis. The results showed that the visual absorption of photons of mixed spectral light and the visual glimmer reaction of the locusts with migratory spectrum characteristics of the peak wavelength of LED lights, reflected the degree of the visual photosensitivity to light photons absorbed by the eye. The visual photosensitive response intensity and the phototactic aggregation effect stimulated by violet light were the most effective, showing that violet light of locusts visual trending sensitivity was consistent with the short sensitive spectrum light of insects visual electrophysiology, whereas the timeliness of the visual photosensitivity reaction and the induction effect was superior under orange light, showing that the biological behavior of locusts visual physiology reaction caused by orange light regulating locusts light rhythm was complicated. Moreover, weak light resulted in stronger visuospatial orientation in terms of the phototaxis of locusts and stronger light resulted in the better visual orientation towards the light source. The results indicated that optical wave properties could affect the visual absorption of spectral light photons, which resulted in different visual responses to different optical frequency energies and restricted the visual bio-photosensitive induction activity of locusts. The study provides new understanding of positive and negative phototaxis of locusts and useful data for the further development of photoelectric induction techniques for the control of locusts. Keywords: locusta migratoria, visual reaction effect, phototactic bio-behavior, light property, bio-control DOI: 10. 25165/j.ijabe.20171004.2357 Citation: Liu Q H, Xin Z, Zhou Q. Influences of visual reaction effect induced and stimulated by different lights on phototactic bio-behaviors in Locusta migratoria manilensis. Int J Agric & Biol Eng, 2017; 10(4): 173–181.